Browser-based software for technology transfer - Bishop, Judith; Halleux, Jonathan "Peli" de; Tillmann, Nikolai; Horspool, Nigel; Syme, Don; Xie, Tao (SAICSIT '11 Proceedings of the South African Institute of Computer Scientists and Information Technologists Conference on Knowledge, Innovation and Leadership in a Diverse, Multidisciplinary Environment, 2011)
Technology transfer is typically viewed as being from academia to industry but it can indeed go in either direction. Many of the same challenges then apply - platform suitability, timeliness, support, and community building. In this paper, we describe recent efforts to transfer technology for research and teaching from an industrial research laboratory to universities, and discuss some of the key success factors and major challenges. Examples quoted include Try F# and Pex4Fun.